1999
DOI: 10.1111/j.1572-0241.1999.935_q.x
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial Comparing Ciprofloxacin With Mesalazine for The Treatment of Active Crohn's Disease

Abstract: This study suggests that ciprofloxacin 1 g/day is as effective as mesalazine 4 g/day in treating mild to moderate flare-up of Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…Several randomized clinical trials have evaluated the efficacy of these antibiotics, used alone or in combination, at inducing remission in CD (table 2) [35,37,38,39,40,41,42]. The results of these studies have shown that patients with colonic localization get more benefit from antibiotics, probably because of the higher bacterial concentration in the colon than in the small bowel.…”
Section: Antibiotics As a Treatment Of Inflammatory Bowel Diseasementioning
confidence: 99%
“…Several randomized clinical trials have evaluated the efficacy of these antibiotics, used alone or in combination, at inducing remission in CD (table 2) [35,37,38,39,40,41,42]. The results of these studies have shown that patients with colonic localization get more benefit from antibiotics, probably because of the higher bacterial concentration in the colon than in the small bowel.…”
Section: Antibiotics As a Treatment Of Inflammatory Bowel Diseasementioning
confidence: 99%
“…Again, subgroup analysis suggested a benefit of antibiotic therapy in patients with colonic involvement (53% remission in the antibiotics group vs. 25% in the placebo group, p = 0.10). Two additional studies showed no difference between ciprofloxacin and mesalazine [42], and between ciprofloxacin plus metronidazole and 6-methylprednisolone [43]. Due to the small sample size, there is a high risk of type II errors in these studies that did not have a design adequate for equivalence studies.…”
Section: First-line Treatment Optionsmentioning
confidence: 99%
“…After 6 weeks, both treatments were equally effective, the remission rate being 56 and 55% in patients receiving ciprofloxacin or mesalamine respectively [36]. In a small study [37], ciprofloxacin was shown to be effective in association to standard treatment in patients with resistant disease.…”
Section: Studies In Patients With Crohn’s Diseasementioning
confidence: 99%